Solving and Verifying the Boolean Pythagorean Triples Problem via Cube-and-Conquer - Oliver Kullmann (Theory and Applications of Satisfiability Testing – SAT 2016, 2016)
We solved a long-outstanding open problem in Ramsey theory, using SAT solving.